2022
DOI: 10.1093/annweh/wxac006
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Cleaning Agents’ Health Hazards and Occupational Injuries and Diseases Attributed to Them in Sweden

Abstract: Using data from the Swedish Products Register, hosted by the Swedish Chemicals Agency (KemI), national occupational injury and disease statistics, and call records from the Swedish Poisons Information Centre (PIC) we characterize health hazards of marketed cleaning products and recorded injuries, disease, and incidents linked to cleaning or disinfection agents. The results show that cleaning agents pose many kinds of health hazards, although corrosion and irritation hazards dominate, in particular for the eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…This study also found that about a third of the participants experienced respiratory problems after working in their school, and about a third were relieved of symptoms, i.e., symptoms went away after leaving the school premises. This speculatively could be consistent with the idea that CSDPs are irritating to the respiratory tract, and after leaving the area in which these products are used, one can experience symptom relief [5,6,15,24]. This is not consistent with sick building syndrome, where "most" people in a building will feel ill and "most" will feel better after leaving the building [36].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This study also found that about a third of the participants experienced respiratory problems after working in their school, and about a third were relieved of symptoms, i.e., symptoms went away after leaving the school premises. This speculatively could be consistent with the idea that CSDPs are irritating to the respiratory tract, and after leaving the area in which these products are used, one can experience symptom relief [5,6,15,24]. This is not consistent with sick building syndrome, where "most" people in a building will feel ill and "most" will feel better after leaving the building [36].…”
Section: Discussionmentioning
confidence: 72%
“…A 2020 literature review reported that there was no significant transmission of COVID-19 through inanimate surfaces but agreed people should use disinfectant products [4]. In general, CSDPs have health risks when exposure occurs, i.e., if inhaled or if they get on the skin [1,[5][6][7][8][9][10][11][12][13]. These products, whether volatized or aerosolized, can be considered indoor air pollutants [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los productos de limpieza son mezclas de muchos ingredientes químicos y se asocian con irritaciones de las vías respiratorias inferiores como asma (Ahmed et al, 2022), EPOC, rinitis crónica (Dumas, 2021) y lesiones en la piel como quemaduras químicas (Kathare et al, 2022). La exposición a polvo de madera se asocia con cáncer de nasofaringe y senos paranasales (Mofidi et al, 2022).…”
Section: Estilistasunclassified
“…These chemicals have the potential to cause allergic contact dermatitis. In addition, these irritants may lead to impairment of skin barrier function, leading to ICD [21, 22]. Occupational groups (such as shampoo workers and medical staff.)…”
Section: Introductionmentioning
confidence: 99%